(untitled) (Plant Tissue Culture and Biotechnology, 2014)
Artemisinin, an important antimalarial drug against multidrug resistant strains of Plasmodium, can be produced in Artemisia annua L. Field production of artemisinin is affected by environmental condition and geographical location. In vitro production via cell suspension culture is an alternative mode and cell line selection is important to ensure sustainable production of biomass and artemisinin. Callus cell lines were derived from the leaf explants of five A. annua clones grown in two different locations in Vietnam. Thirty-four callus cell lines with consistent growth index (GI) were selected from these five clones and were categorized into fast (GI > 20), intermediate (GI 15 - 20) and slow (GI < 15) growing groups. The selected lines were found to have different morphology in term of colour and texture. The callus texture did affect the cell growth of A. annua in which the friable callus type showed faster, consistent and sustainable cell biomass production. D. O. I.http://dx.doi.org/10.3329/ptcb.v23i2.17507 Plant Tissue Cult. & Biotech. 23(2): 157-163, 2013 (December)